The Role of Service Quality on Subjective Well-Being of Students, With Mediators of Satisfaction and Customer Company Identification - Muhamad Singgih Pradipto; Albari Albari (Jurnal Manajemen Indonesia, 2021)
The level of service quality is often a shared measure between providers and users of products for transactions. High quality demands by service users can make service providers to implement an effective work culture. For service users, quality can be used as a basis for assessing satisfaction after receiving service. Using certain services can also arouse the customer's self-perception that he is fit to consume the service produced by providers who are committed to quality. High results from quality, satisfaction, and self-identification of users at service providers become the basis for users to conduct subjective well-being evaluations from time to time. The relationship between these variables was disclosed in this study. This study used a survey method, with a population of students who were still actively studying at 6 universities in DIY. A total of 166 students were selected by convenience sampling method to serve as research samples. By using regression analysis and the SPSS program, it can be proven that there is an indirect effect of service quality on subjective well-being. The results showed that satisfaction and customer-company identification have very important roles, because both variables function as mediators of the influence of service quality on subjective well-being, but satisfaction has a more dominant role than customer identification. From the results of this study it is suggested that universities need to pay attention to the closeness of the relationship with their students, but what is more important is to increase their satisfaction with overall services, such as when they are on campus. Keywords-- service quality, satisfaction, customer-company identification, subjective well-being